2018
DOI: 10.3989/pirineos.2018.173004
|View full text |Cite
|
Sign up to set email alerts
|

Évolution recente des glaciers du Vignemale (2013-2017)

Abstract: [fr] Les glaciers d’Ossoue, du Petit Vignemale et des Oulettes sont les trois derniers glaciers du massif du Vignemale. Le plus grand d’entre eux, le glacier d’Ossoue, est l’un des mieux documentés dans les Pyrénées. Son évolution est un indicateur précieux des fluctuations du climat au sud-ouest de l’Europe. Une étude précédente de reconstruction du glacier d’Ossoue s’arrêtait en 2013 (Marti et al., 2015a). Nous présentons ici une mise à jour de son bilan de masse entre 2013 et 2017. Une carte de changement d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(25 reference statements)
0
2
1
Order By: Relevance
“…Indeed, the loss of 23.2% (2.60% per year) of the glacierized area in the period 2011-2020 is similar to the rates of loss of 2.93% per year and 2.59% per year reported for the periods 2008-2016 (Rico et al, 2017) and 1984-2008(Rico, 2019, respectively. The mass balances of −0.70 and −1.03 m w. e. yr −1 for Maladeta and Ossoue glaciers do not differ substantially from previously reported mass balances (Gascoin & René, 2018;. Also, the area-weighted mean ice thickness loss of 0.70 m yr −1 reported here is somewhat smaller but in the same order of magnitude compared to values reported by Hugonnet et al (2021) in Central Europe (−1.00/−1.11 ± 0.23/0.26 m yr −1 in the periods 2010-2014/2015-2019, respectively for a much wider region).…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…Indeed, the loss of 23.2% (2.60% per year) of the glacierized area in the period 2011-2020 is similar to the rates of loss of 2.93% per year and 2.59% per year reported for the periods 2008-2016 (Rico et al, 2017) and 1984-2008(Rico, 2019, respectively. The mass balances of −0.70 and −1.03 m w. e. yr −1 for Maladeta and Ossoue glaciers do not differ substantially from previously reported mass balances (Gascoin & René, 2018;. Also, the area-weighted mean ice thickness loss of 0.70 m yr −1 reported here is somewhat smaller but in the same order of magnitude compared to values reported by Hugonnet et al (2021) in Central Europe (−1.00/−1.11 ± 0.23/0.26 m yr −1 in the periods 2010-2014/2015-2019, respectively for a much wider region).…”
Section: Resultscontrasting
confidence: 61%
“…Glacierized area losses and thickness loss for the different glaciers are highly heterogeneous, confirming that glacier area cannot be used as a proxy for mass balance . As recent research and the results of this study demonstrate, TLS surveys (Fischer et al, 2016;López-Moreno et al, 2019), UAV surveys (Gaffey & Bhardwaj, 2020;Revuelto et al, 2021) and new emerging remote-sensing products such as high resolution satellite stereo imagery (Gascoin & René, 2018) are efficient tools for analyzing the evolution of very small glaciers. The increased use of optical satellite imagery with enhanced resolution and frequency may permit better delimitation of glacierized areas, and the identification of crevasses, debris cover and the evolution of the ELA, finally allowing an improved monitoring of even very small glaciers .…”
Section: N N Nmentioning
confidence: 76%
“…Various studies of other glaciers in the Pyrenees have also shown a continuous increase in glacier thickness and area loss, with a high interannual variability but a clear negative trend over longer time periods. These works focused on Monte Perdido Glacier (López- Moreno et al, 2019), Ossoue Glacier (Gascoin and René, 2018), Maladeta Glacier (Pastor Argüello, 2013) and La Paul Glacier (Rico et al, 2015). The mean annual specific mass balance values of −0.6 m w.e.…”
Section: Resultsmentioning
confidence: 99%